A quarantine paradox: understanding Gender-Based Violence (GBV) in post-COVID-19 era: insights from Golden Valley mining community, Zimbabwe - Everjoy Magwegwe (BMC, 2024)
Abstract The COVID-19 pandemic has brought unprecedented challenges globally, with a notable surge in gender-based violence (GBV) incidents. This descriptive, exploratory study conducted in the Golden Valley mining community in Kadoma, Mashonaland West Province, Zimbabwe, delves into the challenges faced by GBV survivors during and after the pandemic, alongside community perceptions of GBV in the post-COVID-19 era. Guided by Bronfenbrenner's Social-Ecological Model which offers insights into the various levels of influence on GBV behavior and experiences,aiding in the development of contextually relevant prevention strategies. The study used qualitative methods such as interviews and focus group discussions, there were 24 study participant classified by random and convenient sampling techniques including traditional and community leaders, gbv surviours medical personnel and male and female, community members. The research followed the COREQ guidelines to transparently document the research process and findings. The research sheds light on the multifaceted nature of GBV exacerbated by societal norms and economic instability in a low-income, masculine-dominated work culture experience in the COVID-19 period. Findings underscore the urgent need for comprehensive prevention programs, effective legislation, and community engagement to address GBV in post-pandemic communities. The research provides valuable lessons for enhancing GBV prevention efforts globally, emphasizing the significance of survivor voices and addressing root causes of GBV.